Multiple organ resection for large paraganglioma a case report - Farkasova, M; Procházka, V; Kunovsky, L; Eid, M; Vlazny, J; Hustý, J; Balko, J; Kysela, P; Kala, Z (Rozhledy v chirurgii, 2021)
Paragangliomas represent a group of neuroendocrine tumours which occur in various localizations. Most of them produce catecholamines, and in advanced cases present with typical symptoms and signs such as palpitations, headache and hypertension. The only curative treatment is radical resection. About one-quarter of paragangliomas are malignant, defined by the presence of distant metastases. There are multiple treatment options for unresectable metastatic tumours. They include radionuclid therapy, chemotherapy, and radiotherapy, although none of them are curative. Cytoreductive surgery can also be considered, especially when the goal is to decrease symptoms related to advanced disease. We present a rare case of a large paraganglioma of the left retroperitoneum. Despite radical surgery, early recurrence of the disease was observed.
Keywords: Paraganglioma; neuroendocrine tumours; surgery; paraganglioma; Humans; lidé; oncology; multiple organ resection; paragangliom